High-Fiber Diet or Combined With Acarbose Alleviates Heterogeneous Phenotypes of Polycystic Ovary Syndrome by Regulating Gut Microbiota - Wang, Xuejiao; Xu, Ting; Liu, Rui; Wu, Guojun; Gu, Liping; Zhang, Yahui; Zhang, Feng; Fu, Huaqing; Ling, Yunxia; Wei, Xiaohui; Luo, Yunchen; Shen, Jian; et al. (Frontiers in Endocrinology, 2022)
Objective: Gut microbial dysbiosis is associated with the high heterogeneity of polycystic ovary syndrome (PCOS), however, studies about gut microbiota targeted clinical intervention in PCOS are limited. Our study aimed to evaluate the effects of high-fiber diet or combined with acarbose on the clinical phenotypes of PCOS, focusing on the possible influence of gut microbiota in this process. Methods: 25 patients with PCOS were recruited and randomly divided into two groups, W group (n=14) received the WTP diet (a high-fiber diet composed of whole grains, traditional Chinese medicinal foods, and prebiotics), and A group (n=11) received the WTP diet combined with acarbose. The follow-up time was 12 weeks. The sex hormonal and glycolipid metabolic parameters, inflammatory factors, brain-gut peptides and alteration of gut microbiota were evaluated. Results: The PCOS clinical phenotypes, inflammatory state and brain-gut peptides secretion were all alleviated in both groups, while the hyperandrogenism, insulin resistance and brain-gut peptides secretion were better improved in the A group. Alpha and beta diversity were altered more significantly in the A group. Amplicon sequence variants (ASVs) were clustered into 14 co-abundant groups (CAGs) as potential functional groups that may respond the intervention. The CAGs predominantly comprised of Bifidobacterium and Lactobacillus were more enriched, while the CAGs predominantly comprised of Bacteroides vulgatus, Alistipes, Blautia, Lachnospira and Roseburia were more inhibited in the A group than W group. Moreover, the CAGs enriched in the A group had a stronger negative correlation with the LH/FSH ratio, testosterone, HOMA-IR, α-AGP and leptin, and positive correlation with adiponectin and spexin, while the CAGs inhibited showed an opposite trend. Conclusions: High-fiber diet could alleviate the chronic metabolic inflammation, reproductive function and brain-gut peptides secretion of patients with PCOS, and high-fiber diet combined with acarbose could better improve the PCOS clinical phenotypes. The remodeling of gut microbiota by our intervention may play an important role in these improvements.